Exploring the Gut Microbiome's Influence on Colorectal Cancer Development and Management: A Review of Current Knowledge and Future Directions - Grela, Wiktor; Niewiadomska, Jagoda; Furtak, Daria; Tulej, Dawid; Głogowska, Paulina; Dziedzic, Alicja; Gniaź, Natalia; Marciniuk, Dominika; Marko, Natalia; Górska, Aleksandra (Journal of Education, Health and Sport, 2024)
Introduction Colorectal cancer (CRC) is a significant global health concern, ranking as the third most commonly diagnosed cancer and the second leading cause of cancer-related deaths worldwide, with over 1.9 million new cases and nearly 935,000 deaths annually. The rise in CRC incidence is attributed to various lifestyle changes, including dietary shifts, sedentary behavior, and increased obesity rates. These factors underscore the urgent need for new preventive strategies targeting the underlying mechanisms of CRC development. Purpose This review evaluates the intricate relationship between the gut microbiome and CRC, aiming to enhance our understanding of how microbial diversity and composition contribute to CRC pathogenesis. State of Knowledge Studies reveal a correlation between the onset and progression of CRC and changes in microbial diversity and specific taxa. In CRC patients, the presence of Fusobacterium nucleatum is linked to inflammation and poor prognosis, while Bacteroides fragilis is associated with promoting colitis and carcinogenesis. The Human Microbiome Project's findings reveal that unique microbial communities can impact inflammation and tumor growth. Meta-analyses underline the crucial role of microbial diversity, influenced by diet and health status, in cancer prevention and progression, particularly in CRC. Conclusions Understanding the interactions between the microbiome, diet, and host health is crucial for developing targeted treatment strategies and precision diagnostics for CRC. Insights from microbiome research could significantly improve patient outcomes in CRC management. Further high-quality studies are essential to fully elucidate the therapeutic potential of the microbiome in CRC treatment.